Effect of Lactic Acid Bacteria Fermentation on Quality, Flavour and Antioxidant Activity of Rice Milk - Xiaomei GAO; Yong SUI; Zhenzhou ZHU; Shuyi LI; Lei ZHOU; Jianbin SHI; Tian XIONG; Fang CAI; Xin MEI (Shipin gongye ke-ji)
In order to explore the effects of lactic acid bacteria fermentation on the quality, flavour and antioxidant activity of rice milk, different rice varieties (black rice, red rice and brown rice), auxiliary ingredients (milk powder and sucrose) and lactic acid bacteria were used to produce rice milk in this study. The stability, protein content, reducing sugar content, total phenolic content, DPPH· and ABTS+· scavenging activity, and volatile flavor compounds of fermented and non-fermented rice milk were evaluated. The results showed that the acidity, protein content, total phenolic content and antioxidant activity of rice milk increased significantly after fermentation by lactic acid bacteria, while the pH, soluble solids and reducing sugar content decreased significantly (P<0.05), and the centrifugal precipitation rate did not change significantly. The results of gas chromatography-mass spectrometry (GC-MS) and electronic nose (E-nose) analyses showed that the types and contents of flavouring substances were significantly higher in the rice milk fermented by lactic acid bacteria compared to the control. The contents of n-hexanol and benzaldehyde, which were the main aroma components of rice milk increased by 0.23%~2.42% and 0.11%~0.72%, respectively. And the rice milk fermented by lactic acid bacteria had a unique fermented flavour. The results of this study could provide a theoretical basis for the in-depth understanding of the effects of lactic acid bacteria fermentation on the quality, antioxidant activity and volatile flavour substances of rice milk.